A literature review on accounting higher education institute performance in China: The role of AI and technology readiness - Mengrong, Han; Mustafa, Hasri; Kharuddin, Saira (International Journal of Innovative Research and Scientific Studies, 2025)
This research offers a systematic and comprehensive literature review analyzing current studies on the performance of higher education institutes in China through the incorporation of technological advancements. This systematic literature review method involves 34 peer-reviewed articles published in reputable academic journals between 2012 and July 2023. This study is confined to a review of empirical papers derived from digital databases encompassing the terms "artificial intelligence or innovation or technological advancement in higher education institutes in China" in the titles. This study proposes a framework to assess the performance of higher education institutes. Further, artificial intelligence is proposed as a mediator, and technology readiness is proposed as a moderator. Significant literature gaps indicate that this field is a relatively novel phenomenon. Thus, rigorous research on the topic proves necessary to develop a holistic understanding of the subject area. This study expands the current body of knowledge by providing the first comprehensive systematic review of the performance of higher education institutes and recommending future research agendas.